A Global Collaborative Comparison of SARS-CoV-2 Antigenicity Across 15 Laboratories - Polina Brangel; Sina Tureli; Barbara Mühlemann; Nicole Liechti; Daniel Zysset; Olivier Engler; Isabel Hunger-Glaser; Ioana Ghiga; Giada Mattiuzzo; Isabella Eckerle; Meriem Bekliz; Annika Rössler; et al. (Viruses)
Setting up a global SARS-CoV-2 surveillance system requires an understanding of how virus isolation and propagation practices, use of animal or human sera, and different neutralisation assay platforms influence assessment of SARS-CoV-2 antigenicity. In this study, with the contribution of 15 independent laboratories across all WHO regions, we carried out a controlled analysis of neutralisation assay platforms using the first WHO International Standard for antibodies to SARS-CoV-2 variants of concern (source: NIBSC). Live virus isolates (source: WHO BioHub or individual labs) or spike plasmids (individual labs) for pseudovirus production were used to perform neutralisation assays using the same serum panels. When comparing fold drops, excellent data consistency was observed across the labs using common reagents, including between pseudovirus and live virus neutralisation assays (RMSD of data from mean fold drop was 0.59). Utilising a Bayesian model, geometric mean titres and assay titre magnitudes (offsets) can describe the data efficiently. Titre magnitudes were seen to vary largely even for labs within the same assay group. We have observed that overall, live Microneutralisation assays tend to have the lowest titres, whereas Pseudovirus Neutralisation have the highest (with a mean difference of 3.2 log2 units between the two). These findings are relevant for laboratory networks, such as the WHO Coronavirus Laboratory Network (CoViNet), that seek to support a global surveillance system for evolution and antigenic characterisation of variants to support monitoring of population immunity and vaccine composition policy.